(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
In accordance with the Resolution of the Cabinet of Ministers of the Republic of Uzbekistan dated March 28, 2025 “On additional measures for the effective use of household plots and peasant farms”, effective work is also being carried out in the Shorchi district of the Surkhandarya region of the Republic of Uzbekistan.